Komparasi Bentuk Negara dan Batasan Kekuasaan pada Konstitusi di Indonesia, Amerika Serikat, dan Swiss - Razak, Muhamad Abdul; Septaviana, Diana (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
Various countries of the world certainly have constitutions, since constitutions are one of the first few conditions for the establishment and development of an independent nation, and so is its genes in countries' existence. Constitutions are enacted in countries around the world including Indonesia, the United States, and Switzerland. Indonesia became interesting to study. The United States, and Switzerland are countries of the world that have a constitution. The constitution became essential to Indonesia, the United States, and Switzerland. Indonesians. Research used the normative- juridical kind of study to find rules of law, principles of law, or legal doctrines to provide answers to the legal issues at hand. The first will be discussed on the constitutionality of the state. According to the constitution Indonesia acknowledges the existence of a united state. While the federal system structure of the United States has developed over a long period of time. While in Switzerland, the constitution and federal laws ensure cantonese autonomy with the principle of subsidies ensure that all duties not explicitly assigned to the federal level are in cantonese responsibility. The next aspect considered is the difference between constitutional restrictions and supervision of power in Indonesia, the United States, and Switzerland.